[PP.32.19] CARDIOVASCULAR RISK ASSESSMENT AND SOCIAL FRAMEWORK OF COMMUNITY OF CAPE VERDEAN UNIVERSITY STUDENTS STUDYING IN PORTUGAL. (September 2016) - Tavares, L.; Calhau, C.; Polonia, J.
Abstract : Objective: Migration of populations of African to Europe poses problems of adaptation and health risk Cardiovascular disease is the leading cause of mortality and population of African appears to have greater risk We evaluate the cardiovascular risk profile in Cape Verde University population studying in Portugal compared to Cape Verdean population equivalent to live in Cape Verde and Portuguese equivalent Caucasian population living in Portugal Design and method: A cross-sectional study comparing 3 University populations aged between 19–25 years: Cape Verde to study in Portugal (CV-EN), Cape Verde equivalent to live in Cape Verde (CV-CV), Portuguese Caucasian living in Portugal (PT-PT). Anthropometric assessment was made, blood pressure (media 3 records), the pulse wave velocity (PWV), the mcroalbuminuria (MA micg/mg creatinine) and urinary excretion of sodium estimated for 12:00 am (Kawasaki) Results: For similar ages 22.5 + 2.6 years, n = 104, 54% women (CV-EN); 24.9 + 3.3, n = 100, 62% women (CV-CV), 23.5 + 3.0 years, 67% women (PT-PT), in the comparison between groups (ANOVA) the IMC in CV-EN (22.9 + 3.5 Kg/m 2 ) was higher (p = 0.018) than CV-CV (21.9 + 3.8) and PT-PT (21.6 + 3.1), blood pressure (mmHg) was higher (p = 0.001) in CV-EN (119/73 + 12/7) and CV-CV (121/73 + 15/9) that in PT-PT (107/69 + 14/8), the PWV (m/s) was higher (p = 0.04) in CV-EN (8.7 + 1.1) and CV-CV (8.8 + 1.8) than in PT-PT (8.0 + 1.2), MA (micg/mg creatinine) was higher (p = 0.04) in CV-EN (13.0 + 63.2) and CV-CV (9.2 + 25.1) than in PT-PT (5.8 + 6.4), and excretion of sodium (mmol/24 h) was higher (p = 0.001) in CV-EN (235 + 91) and CV-CV (197 + 85) that in PT-PT (194 + 90) while this trend was maintained while comparing genders separately Conclusions: Cape Verdean student population (with greater tendency for those resident in Portugal) presents BP values, arterial stiffness, albuminuria and salt intake higher than the Caucasian counterparts. The increased cardiovascular risk associated with these particular measures to combat justifies populations the modifiable risk factors and the promotion of hygiene habits.